Perceptions and attitudes towards the teaching of English pronunciation in efl teacher training programmes in Chile - Rodríguez Escobar, Claudia (Lenguas Modernas, 2023)
English teachers are usually asked which one is better whether British or American English. There seems to be a perceived idea that only those two varieties are representative of the English language given that they are traditionally the ones taught in schools and university programmes in Latin America. The purpose of this qualitative case study is to know and understand the attitudes and perceptions a group of 12 EFL university teachers from Chile have towards British and American dialects as models for teaching pronunciation. It also focuses on the perception and beliefs they have about including other less popular English dialects in their teaching practice, and the instructional approach used when teaching pronunciation in a remote classroom as a consequence of the COVID-19 pandemic. Results show that even though world Englishes are considered an important element to bear in mind, there is still a strong tendency to remain in the lane of British vs American English. The study also reveals that relying on technology as a forced methodology during the pandemic has had a positive impact as it has helped enhancing students’ autonomy and metacognition